Geometria e construção civil: perspectivas de alunos do ensino fundamental de uma escola em Tanguá/RJ - Teixeira, Rafael Motta (2017)
The main objective of this work is to investigate whether the tacit knowledge of Civil Construction workers can help the learning of Geometry, regarding the differentiation between solids and polygons, of regular elementary students in the seventh year; This work was based on Van Hiele's Theory of Geometric Thought, and a qualitative research methodology based on the Didactic Engineering of Michèlle Artigue was used. Information was verified that validated, as data, the basis of the research through actions that occurred in a daily school universe of the students of the second cycle (seventh year) of Elementary School II of a school located in the municipality of Tanguá, part of the metropolitan periphery of the state of Rio de Janeiro. It was identified, as a result of this research, that this professional daily life had a positive impact on the daily school learning, contextualized through actions and facts that occurred in the classroom that referenced the topics addressed in the field of differentiation and characterization of Solids and Geometric Polygons.